Sense of Belonging as an Important Factor in the Pursuit of Physics: Does It Also Matter for Female Participants of the German Physics Olympiad? - Ladewig, Antonia; Keller, Melanie; Klusmann, Uta (Frontiers in Psychology, 2020)
This paper focuses on stereotype threat and its effects on sense of belonging in the German Physics Olympiad science competition. Participants completed questionnaires about sense of belonging, stereotype endorsement, interest, and self-concept in physics, as well as about value and success expectations of studying physics at college. Female participants who endorsed negative stereotypes about female talent for physics felt less sense of belonging to physics. This effect did not manifest for male participants. Sense of belonging to physics significantly predicted value and success expectations for studying physics at college beyond what is predicted by interest and self-concept in physics. These findings suggest that sense of belonging is influenced by stereotype threat, which was shown to cause gender differences in science. Nevertheless, sense of belonging could be included into expectancy-value theory based on its predictive impact on value and success expectations of studying physics.